Karakteristik performance individu muda di Desa Ngablak dan hubungannya dengan penyalahgunaan NAPZA - Suhartini Suhartini; Neni Trilusiana Rahmawati; Yudha Nurhantari; Hendro Widagdo; Idha Arfianti Wira Agni; Martiana Suciningtyas; Wikan Basworo (Journal of Community Empowerment for Health, 2019)
Alcohol, narcotics, psychotropic substances and other addictive substances are substances that are often misused. The majority of drug users are adolescents with age ranging from 13 - 17 years old at which abuse can affect body composition. Considering the role of the younger generation as the nation’s successors, it sparks the urgency to alleviate this negative behavior. One of the measures that can be done is by shifting the negative activities to positive ones such as sports. In order to do this, it is necessary to identify the performance characteristics of the youths to maximize their potential. This study aimed to find out the performance characteristics of the younger generation in Ngablak Village and their association with drug abuse. A total of 50 youth members in Ngablak Village, Ngablak Subdistrict, Magelang Regency were examined for anthropometry, physical (pulse, respiration rate, blood pressure, temperature), and somatotype associated with performance. Identification of subjects involved in alcohol and drug abuse was carried out using a questionnaire. The results were displayed descriptively. Statistical analyses (t-test or Mann Whitney U test) were used to compare performance characteristics between groups. Age of subjects ranged from 9 - 19 years and 50% were male. A total of 13 boys and 2 girls consumed alcohol. The results of physical examination showed the normal range in all subjetcs. The average age, height, and weight of male subjects who comsumed alcohol were higher than those who did not (p < 0,05). There was no difference in somatotype between adolescents who consumed alcohol and those who did not. The body type of male subjects based on measurements was the ideal type, whereas the female subjects had endomesomorphic body type. The tendency of consuming alcohol does not cause differences in body type in adolescents, both in male and female.